Réponses

Meilleure réponse !
2013-04-06T10:41:55+02:00
1) A = (2x-3)^-(4x+7)(2x-3)
A = 4x^-12x + 9 -(8x^ -12x +14x -21)
A = 4x^ -12x + 9 - 8x^ + 12x - 14x +21
A = ....(apres tu calcules en regroupant les x^ ,les x et les numeriques..)
2) A= (2x-3)^ -(4x+7)(2x-3)
A= (2x-3)[(2x-3)-(4x+7)]
A = (2x-3)(2x-3-4x-7)
A = (2x-3)(2x-10)
3) pour x = 0
A = (2x-3)(2x-10)
A = (2X0-3)(2X0-10)
A = 30
Pour x = -5
A =(2x-3)(2x-10)
A = (2X(-5)-3)(2X(-5)-10)
A = 260
Pour x = 1/2
A = (2x -3)(2x-10)
A = (2X 1/2-3)(2X1/2-10)
A = -2 X (-9)
A = 18

Voilaaaaaa !! Jespere t'avoir aidé ! :D